Pendidikan Kesehatan Gizi Seimbang pada Balita - Suci Utami; Rosmalia Kamil; Dea Riskha Fitriliana (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
Health education is an activity to provide and increase knowledge, good individual, group or community attitudes to maintain and improve their own health Health education on balanced nutrition in toddlers can provide more knowledge about nutrition to parents in order to prevent malnutrition in children under five is a health problem that can affect child development to adulthood, it is very important for parents to understand the dangers of malnutrition and how to prevent it by providing a balanced nutritional diet. The method of implementing Ibm is carried out by the lecture method, and the discussion using lealets while the outcome obtained is the increased awareness and knowledge of parents about balanced nutrition for toddlers in Sutapranan Village. The output obtained was the presence of health education media on balanced nutrition in PKK activities in Sutapranan Village.